Awareness Regarding Vesicovaginal Fistula among Women Residing in A Municipality of Kapilvastu - Gurung, Saraj; Panthi, Vidya; Kachapati, Anuja (Journal of Universal College of Medical Sciences, 2018)
Introduction: Vesicovaginal fistula (VVF) is one of the most distressing maternal morbidities. It is a physically and socially disabling obstetric complication that affects many women annually. It has a devastating social, economic and psychological effect on the health and well-being of the affected women. The aim of the study was to find out awareness regarding vesicovaginal fistula among women. Material and Method: Descriptive study design was used for the study to find out awareness regarding vesicovaginal fistula. Hundred women were selected as the study sample by non purposive and snow ball sampling technique. Pretested semi structured interview schedule was used for data collection and analyzed by using descriptive and inferential statistics. Results: The findings of the study revealed that 81% and 100% of women knew that delivery by non skilled and wetting under garments is risk factor and symptom of VVF. 82% and 73% of women knew that VVF is preventable and curable respectively. 58% of women had knowledge that women can become pregnant in case of VVF and 47 % knew that VVF can be reoccurred. Out of 73 women, 23% knew that surgery as the treatment of VVF. Forty nine percentage of women had answered regarding family and social misbehave and depression (5%) being social consequences of VVF. Seventy percentage of women answered that cervicitis is complication of VVF. Conclusion: Based on the findings of the study half of the women had low knowledge regarding VVF. So, it is recommended to organize continue awareness program to the women regarding VVF.